GENDER DIFFERENCES IN TERMS OF EXPOSURE TO VIOLENCE: A STUDY OF TURKISH ADOLESCENCE - Yorohan, R.; Caliskan, Z. Catay; Ogel, K. (CAMBRIDGE UNIV PRESS, 2012)
20th European Congress of Psychiatry, Prague, CZECH REPUBLIC, MAR 03-06, 2012